THE IMPACT OF GLOBAL RED CHILI PRICE, GLOBAL OIL PRICE AND INDONESIAN RUPIAH EXCHANGE RATE ON THE DOMESTIC PRICE OF RED CHILI IN INDONESIA - Dedi Kusbiantoro; Dian Hendrawan; Sugianto; Muhammad Ilham Riyadh (International Journal of Accounting, Finance and Business, 2023)
The movement of global commodity prices becomes significant during three stages of crisis in the global economy: the crisis in world oil prices, the global financial crisis, and the global food price crisis. These circumstances can have an impact on Indonesia's economic growth. The prices of world oil, global food, and the global financial situation continue to rise, which can affect overall economic growth.The research aims to address the following questions: (1) Does the fluctuation in world oil prices affect the price of Red Chili in Indonesia? (2) Does the fluctuation in the Indonesian exchange rate influence the price of Red Chili in Indonesia? (3) Does the world price of Red Chili affect the domestic price of Red Chili in Indonesia? The research utilizes secondary time series data from 1980 to 2021, focusing on the commodity of Red Chili. Data analysis method used is multiple linear regression model. The estimation results indicate that international factors, such as world oil prices, have a significant positive impact on the domestic price of Red Chili. The exchange rate of the Indonesian Rupiah also has a significant positive influence on Red Chili prices in Indonesia. However, the world price of Red Chili has a negative and insignificant effect on domestic prices. The fluctuations in Red Chili prices result from imbalances between food supply and demand. To stabilize food prices, it is crucial to increase productivity, improve access to food supplies, enhance infrastructure, especially transportation and storage facilities, and empower farmers through financial and technical support.Moreover, increasing production, improving distribution and market operations are necessary to reduce price fluctuations of food commodities. The government should respond to export opportunities to strengthen price stability in the domestic market. Additionally, ensuring consumer protection with fair prices and supporting necessary subsidy programs can contribute to stabilizing food prices.